Russian-language publication activities of medical researchers during the COVID-19 pandemic: results of the year - O. T. Kim; O. M. Drapkina; Yu. V. Rodionova (Российский кардиологический журнал)
Aim. To study the dynamics and patterns of medical publications in Russian, made during the year from February 2020, in order to assess the completeness of data on the etiology, pathogenesis, prevention and treatment of coronavirus disease 2019 (COVID-19), as well as rehabilitation and healthcare management during a pandemic.Material and methods. We searched for publications using the Pubmed database and the Elpub platform. The search was carried out using the following requests: “COVID-19” and “SARS-CoV-2”. Thematic sections were allocated according to source type, specialization and research design. The publications were classified according to keywords and meaning. The publication time was estimated by the date it was accepted for publication. Values were assessed using numerical values and graphs.Results. One hundred fifteen (28,5%) publications presented data from original research, while 288 (71,5%) — reflected the results of already existing sources. An increase in proportion of primary sources with the pandemic spread was established. There were following most common study designs: case series — 87 (77,7%); case reports — 15 (13,4%); cohort studies — 8 (7,1%); randomized clinical trials — 2 (1,8%). By topic, the largest number of articles are devoted to the diagnosis and treatment of COVID-19 — 250 (62%), epidemiology — 36 (8,9%), etiology and pathogenesis — 36 (8,9%), healthcare management — 30 (7,4%), “Other” — 20 (4,9%), and policy papers from expert communities — 13 (3,25%). The smallest number of publications is directly related to cardiology and prevention, including immunoprophylaxis — 12 (2,9%), as well as rehabilitation — 6 (1,5%).Conclusion. The dynamics and patterns of publications on COVID-19 in Russian are generally in line with global trends and reflect the pandemic characteristics in Russia. Due to disease novelty, there is currently a knowledge gap in the treatment, prevention and long-term outcomes of COVID-19. In the future, studies with a higher evidence level are needed on possible methods of treatment, prevention, including cardiology issues and vaccination, as well as rehabilitation.